PENGARUH LITERASI PAJAK TERHADAP KESADARAN PAJAK MAHASISWA S1 AKUNTANSI UNIVERSITAS AWAL BROS (UAB) - Desti Monika Uli. S; Wulan Oktaviani; Helmiati Helmiati; Rani Munika; Kasmadi Kasmadi (Jurnal Akuntansi Kompetif, 2026)
This research is motivated by the importance of understanding the tax system for undergraduate Accounting students as prospective accountants who play a crucial role in ensuring tax compliance and effective management of tax funds for national development. This study aims to evaluate the relationship between tax literacy and tax awareness of undergraduate Accounting students at Awal Bros University (UAB) and to identify other factors that influence tax awareness. The method used is a literature study by analyzing various relevant literature sources. The results show that tax literacy has a positive and significant influence on student tax awareness. The higher the level of student understanding and knowledge regarding taxation, the higher their awareness in fulfilling their tax obligations. This finding is in line with previous studies that reveal the importance of tax education in improving taxpayer compliance. Therefore, universities and tax authorities need to collaborate to design effective tax literacy programs for students as future taxpayers. Keywords: tax literacy, tax awareness, undergraduate accounting students